Panicle Trait Diversity and Its Impact on the Productivity of Indonesian Foxtail Millet (Setaria italica L. Beauv.) Genotypes - Luthfiani, Marisa Vidya; Pahlevi, M Reza; Purwoko, Bambang Sapta; Ardie, Sintho Wahyuning (Bogor Agricultural University, Indonesia, 2026)
Foxtail millet is a climate-resilient cereal crop that is growing in importance in food security and sustainable agriculture. This study aimed to identify panicle traits associated with yield, determine functional traits suitable for selecting high-productivity genotypes, and classify superior local Indonesian foxtail millet genotypes. Eight genotypes were evaluated using a randomized complete block design with three replications. Correlation analysis of 31 panicle traits revealed that grain filling rate, panicle weight, grain weight per panicle, grain weight per plant, and grain numbers on the middle and lower primary branches were positively associated with yield. Several of these traits also exhibited high broad-sense heritability and moderate GCV and PCV values, indicating their potential for selection. Principal component and two-way heatmap cluster analyses identified Buru, ICERI-7, Hambapraing, and Mauliru-2 as high-yielding genotypes. The findings provide critical insights for foxtail millet breeding programs in Indonesia focused on improving yield.